2021
DOI: 10.3390/su13179835
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Controlled Drainage on the Content Change and Migration of Moisture, Nutrients, and Salts in Soil and the Yield of Oilseed Sunflower in the Hetao Irrigation District

Abstract: Controlled drainage (CD) is an important agricultural measure for maintaining soil moisture and nutrients, controlling groundwater level, and increasing crop yield. In arid regions, CD can be used to improve the water supply in agriculture and reduce environmental pollution. In this study, we investigated the effects of CD, including drainage depths of 40 cm (CWT1) and 70 cm (CWT2) during the plant growth stages, free drainage (FD), and open-ditch drainage (OD), on the migration of water, nutrients, and salts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…The probability of retaining plant-available soil water due to CTD is lower in our drier study site than in humid sites, but even a small increase in soil water availability associated with the elimination of drainage runoff is important for stabilizing or slightly increasing crop yields. For instance, Dou et al [74] identified a delay in groundwater table decline through CTD (drainage depth of 40 cm) in a dryland area, which allowed sunflower to use groundwater at later growth stages, resulting in yield and water use efficiency improvements of 4.52-11.14% and 1.16-10.8%, respectively. Accordingly, the grain yield of spring barley in our study was increased by 4% in relation to CTD.…”
Section: Discussionmentioning
confidence: 99%
“…The probability of retaining plant-available soil water due to CTD is lower in our drier study site than in humid sites, but even a small increase in soil water availability associated with the elimination of drainage runoff is important for stabilizing or slightly increasing crop yields. For instance, Dou et al [74] identified a delay in groundwater table decline through CTD (drainage depth of 40 cm) in a dryland area, which allowed sunflower to use groundwater at later growth stages, resulting in yield and water use efficiency improvements of 4.52-11.14% and 1.16-10.8%, respectively. Accordingly, the grain yield of spring barley in our study was increased by 4% in relation to CTD.…”
Section: Discussionmentioning
confidence: 99%
“…The effective utilization of water resources and reduction of soil salinization levels have become important influencing factors to achieve high-quality development in agriculture and maintain sustainability in ecology [8,9]. Salinity gradually accumulates in soil during the crop growing season in the Hetao Irrigation District, and the soil can reach moderate or severe salinization by the end of the crop growth period [10]. Ren et al [11] found that the temporal variation in soil salinity was also significant, with the proportion of salt-affected soil at the regional scale increasing from 28% to 42% by the end of the growing season.…”
Section: Introductionmentioning
confidence: 99%
“…Agricultural drainage is an important water management practice that provides a conducive growing environment for root development and crop growth by lowering the water table and removing excess water within the root zone. Although drainage is mainly practiced in humid climates, it is also important in semi-arid climates such as the Canadian Prairies in controlling salinization (Dou et al 2021). The benefits of agricultural drainage are well documented in several textbooks, including increased crop yield and decreased nutrients and drainage outflow (Natural Resources Conservation Service, NRCS 2001, Huffman et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies on CD can be traced to the United States in the 1970s. Due to its enormous benefits, it has been recommended and adopted in various countries, including Canada, Italy, Sweden, Australia, China, and Iran (Wesström et al 2014, Sunohara et al 2016, Tolomio and Borin 2018, Jouni et al 2018, Dou et al 2021.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation